Про-антиоксиданти листків деяких видів тропічних орхідних за низькотемпературної адаптації - Бацманова, Л.М.; Буюн, Л.І.; Ковальська, Л.А.; Таран, Н.Ю. (Інститут ботаніки ім. М.Г. Холодного НАН України, 2008)
Исследовано влияние температуры акклиматизации +25 ºС и +15 ºС на содержание продуктов пероксидного окисления липидов, малонового диальдегида, фотосинтетических пигментов и активность супероксиддисмутазы в листьях Calanthecardioglossa, Cattleyabowringiana, Paphiopedilumappletonianum, полученных в результате семенного размножения в культуре invitro. Показано, что более холодоустойчивыми являются C. bowringiana и P. Appletonianum — для них характерны значительно меньшее усиление интенсивности пероксидного окисления липидов и большая активность супероксиддисмутазы, нежели для C. cardioglossa. The effects of acclimation temperatures +25 ºС and +15 ºС on the content of lipid peroxidation product, malondialdehyde (MDA), photosynthetic pigments and superoxide dismutase (SOD) activities in the leaves of Calanthe cardioglossa, Cattleya bowringiana and Paphiopedilum appletonianum plants, propagated by seeds through in vitro culture, were studied. It has been shown that Cattleya bowringiana and Paphiopedilum appletonianum are the most cold resistant plant species. In the leaves of these species, MDA content increased to lower levels than that seen in the leaves of warm-loving Calanthe cardioglossa. On the contrary, SOD activities were more significant in the leaves of Cattleya bowringiana and Paphiopedilum appletonianum than it was observed in the leaves of Calanthe cardioglossa.